Levels of Affixation in the Acquisition of English Morphology: A Review of Selected Paper - Sikin Nuratika; Nilam Cahaya Fitri Yanti; Ester Mayer (REiLA : Journal of Research and Innovation in Language, 2019)
In considering word formation in language development, there appear to be two central issues which can broadly be characterized as questions relating to (i) productivity, and (ii) constraints. This paper reviews one of the renowned articles which involving the theory of level-ordering that has three levels within the lexicon, children, recognize high-frequency words than low-frequency words written by Peter Gordon (1989), entitled "Levels of Affixation in the Acquisition of English Morphology." This study has three untimed lexical-decision experiments which were carried out with 5- through 9-year-olds of native speakers of English and found general support for a systematic relation between productivity and level assignment. The aim of this paper is to make sure the readers would understand what the article's researcher try to explain about the word-formation such as stem, the stem which add affixes of Level 1, stem which adds affixes of Level 2, and stem which add affixes of Level 3. Moreover, this article's references are accurate (valid) and well-argued. This article is highly recommended for word formation in language development because the researcher stated that children might have a significant part in this process. Therefore, this paper seen the word-formation will be rich in language development depends on how often people actively create words, for example, by combining stems and affixes in much the same way that they generate sentences.